JENIS-JENIS TUMBUHAN PAKU DI KAWASAN WISATA BAYANG SANI KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Yuni, Nora; Nursyahra, Nursyahra; Abizar, Abizar (Pendidikan Biologi, 2014)
ABSTRACTÂ Fern is one of the plants that can be found in the forest and is a group of low level plants with a high level of species diversity. Ferns thrive in temperate climates; they are easily found in the forests. On the side of the road, in the trunk or growing on the soil. Bayang saniâs waterfall is a tourist place with a fairly high humidity that makes lots of ferns grow. Local government will inaugurate this places as a tourism area in south pesisir regency. This situation will be resulted on the construction of larger roads for the visitors who come on tourism sites in baying sani. The development on the reconstruction can be harmful for the plants around the waterfall, especially ferns grown at the edge of the waterfall. This study was conducted from February to March 2014 inÂ  Â theÂ  Â Bayang Â saniâsÂ Â  Tourism Â area,Â Â  bayangÂ  Â subdistrict, Â southÂ  Â pesisir Â regency.Â Â  Further, identification of the sample was conducted at the botany laboratory of biology education program STKIP PGRI of West Sumatra. The research method is the descriptive survey. Data of the research is analyzed descriptively based on the data and description of the species obtained. Based on the research of the types of terrestrial and epiphytic ferns in Bayang saniâs tourism area, Bayang subdistrict,Â  South Â Pesisir Â Regency, Â it Â was Â found Â that Â there Â are Â 21 Â species Â of Â terrestrialÂ  and epiphytic ferns with 14 speciesÂ  Â of terrestrial ferns and 7 species of epiphytic fern which belong to the 2 classes, 11 families, 17 genera, 21 species.Â